The The Social Adjustment and Depression during Outbreak of COVID-19 among Iranian People: The Social Adjustment COVID-19 Pandemic among Iranian People - Zamanian 1*, Faezeh; Foroozandeh 2, Elham (Shahroud Journal of Medical Sciences, 2021)
Background: The sudden outbreak of Corona has created public depression and social changes, which affected countries and communities in terms of psychosocial issues. Social adjustment and physical activity play a very significant role to improve mental health. The purpose of this study was to compare social adjustment and depression during the outbreak of COVID-19 in Iranian employees regarding physical activity participation before the outbreak.Methods: The research method was a causal-comparative type. The statistical population of the study included all men and women over the age of 25 workings in governmental agencies, among which 403 people participated in the online survey by random method. The data about age, occupational, family, and educational condition were collected by demographic questionnaire. Using the short-form depression questionnaire (BDI-13), the depression during an outbreak of COVID-19 was evaluated. A 25-item social adjustment questionnaire (self-made questionnaire) was used for collecting the data of social adjustment specific to new social norms caused by COVID-19.Results: Data analysis using ANOVA showed that active individuals had higher social adjustment than inactive individuals (F = 10.398). Social adjustment was also statistically significant related to depression (r = -0.165).Conclusions: Overall, applying physical activity with the observance of the guidelines approved by the Ministry of Health and other reference institutions will be a great help for the promotion of the social adjustments and mental health.Keywords: COVID-19, Social adjustment, Physical activity, Depression